Analysis of natural stone block pavements in urban shared areas. (June 2018) - Zoccali, Pablo; Moretti, Laura; Di Mascio, Paola; Loprencipe, Giuseppe; D'Andrea, Antonio; Bonin, Guido; Teltayev, Bagdat; Caro, Silvia
Abstract: This paper analysed and verified an existing block stone pavement in an urban shared area. Fatigue and rutting verification was performed respectively for bound and unbound pavement materials using analytical curves available in the literature. The commercial finite element (FE) software Abaqus® was used to calculate the response of the pavement when subjected to different loading, construction and geometrical configurations (i.e. type of analysis, shape and size of meshes, boundary conditions, and bonding contacts between the pavements layers). At the end of this study, a static model of a structure with hexahedral blocks having sides of 0.02 m, with full bonded layers and restrained horizontal displacements on the model sides, was implemented to evaluate the maximum tensile stress induced in a block when the load is applied at its centre. This analysis highlighted the need for rigorous criteria for a correct design, in order to avoid inappropriate and expensive use of road materials.